Beyond ultraviolet radiation: Immune system modulation through skin exposure to visible light and infrared radiation - Garimano, Nicolás Ezequiel (2025)
Sunlight profoundly affects skin health when it is exposed. After acute exposure, a robust inflammatory response is initiated locally. Moreover, chronic exposures lead to carcinogenesis and photoaging. Local and systemic immunosuppression is also triggered after skin irradiation, affecting adaptive immune responses. These effects are mainly produced by the ultraviolet radiation contained in sunlight and were extensively described and reviewed. However, using UV filters during sunbathing and outdoor activities may allow visible light (VL) wavelengths and infrared radiation (IRR) to reach skin cells. Additionally, the employment of therapeutic VL and IR-emitting lasers and LED devices is increasing for various skin conditions. This literature review aims to present current knowledge on the effects of VL and IRR modulating the skin and systemic immune system. These modulations impact healthy skin and can modify immune responses to diverse stimuli in various cell types. According to the wavelength and the dose, VL and IRR increase the production of reactive oxygen species and promote faster wound healing. Moreover, they modulate inflammatory mediators, such as several cytokines and prostaglandins. However, skin exposure to VL can also affect adaptive immune responses. The study of VL and IRR effects on immunity would promote new uses for phototherapy and may establish the need for new strategies in photoprotection.